New inhibitors for the BPTF bromodomain enabled by structural biology and biophysical assay development. Issue 27 (26th June 2020) - Ycas, Peter D.; Zahid, Huda; Chan, Alice; Olson, Noelle M.; Johnson, Jorden A.; Talluri, Siva K.; Schonbrunn, Ernst; Pomerantz, William C. K.
Abstract : We report the first set of small molecule co-crystal structures with the bromodomain of BPTF and describe several new leads for chemical probe development. Abstract : Bromodomain-containing proteins regulate transcription through protein–protein interactions with chromatin and serve as scaffolding proteins for recruiting essential members of the transcriptional machinery. One such protein is the bromodomain and PHD-containing transcription factor (BPTF), the largest member of the nucleosome remodeling complex, NURF. Despite an emerging role for BPTF in regulating a diverse set of cancers, small molecule development for inhibiting the BPTF bromodomain has been lacking. Here we cross-validate three complementary biophysical assays to further the discovery of BPTF bromodomain inhibitors for chemical probe development: two direct binding assays (protein-observed 19 F (PrOF) NMR and surface plasmon resonance (SPR)) and a competitive inhibition assay (AlphaScreen). We first compare the assays using three small molecules and acetylated histone peptides with reported affinity for the BPTF bromodomain. Using SPR with both unlabeled and fluorinated BPTF, we further determine that there is a minimal effect of 19 F incorporation on ligand binding for future PrOF NMR experiments. To guide medicinal chemistry efforts towards chemical probe development, we subsequently evaluate two new BPTF inhibitor scaffolds with our suite of biophysical assays and rank-order compound affinities which could not otherwise be determined by PrOF NMR. Finally, we cocrystallize a subset of small molecule inhibitors and present the first published small molecule-protein structures with the BPTF bromodomain. We envision the biophysical assays described here and the structural insights from the crystallography will guide researchers towards developing selective and potent BPTF bromodomain inhibitors.